THE IMPORTANCE OF INFRASTRUCTURE, FACILITIES AND MANAGEMENT OF THE METAL CASTING WORKSHOP IN THE DEPARTMENT OF MECHANICAL ENGINEERING FT UNNES - yuniarsih, tinna (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
The lack of current infrastructure and facilities conditions results in students practicing outside the department and having to spend funds because of the lack of facilities in the metal casting workshop. The purpose of this study is to explain the layout and management of a good workshop as well as data collection of equipment and materials needed. Using descriptive methods. Data collection using questionnaires to students of the Mechanical Engineering Education Study Program class of 2019, interviews with technicians and lecturers of the Department of Mechanical Engineering, observation, and documentation. Analytical techniques used descriptive analysis techniques. The results of the study show that: (1) a good layout is a layout that meets the standards for the size of the practice room infrastructure and in accordance with the purpose and benefits of making the layout, (2) equipment and materials are tailored to the needs of students, (3) good workshop management is an implementation that applies workshop management knowledge well.